PENGARUH UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Afifah, Nabilah Inayah; Wahyudi, Ickhsanto (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to examine the effect of company size and audit quality on tax avoidance in LQ45 companies on the Indonesia Stock Exchange during the 2018-2021 period. Using a causal research design, 28 LQ45 companies were selected as samples through a purposive sampling method, with a total of 112 financial reports as data. The results of the study show that audit quality has a significant positive effect on tax avoidance, while firm size has no significant effect on tax avoidance. In combination, firm size and audit quality simultaneously affect tax evasion. This study contributes to filling the existing research gap and provides further understanding of the factors influencing LQ45 corporate tax evasion in Indonesia. The results of this study are relevant to practitioners, regulators and academics in managing tax avoidance practices in LQ45 companies in Indonesia.